PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT PANCA BOGA PARAMITA CABANG TANGERANG - Elma Saswita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the partial effect of work discipline on employee performance, the partial effect of work motivation on employee performance, and the simultaneous effect of work discipline and work motivation on employee performance at PT Panca Boga Paramita Tangerang Branch. This study employs an associative quantitative methodology. This study employed a sample size of 60 respondents. The technical analysis and data tests included in this study are as follows: simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, and t and F tests. The results of the multiple linear regression tests yielded a regression equation, Y = (7.999 + 0.290 X1 + 0.713 X2), indicating that work discipline has a significant effect on employee performance (t count 13.583 > t table 1.671) with a significant value (0.001 < 0.005). The results of the hypothesis test regarding work motivation have a significant effect on employee performance (t count 15.518 < t table 1.671) and a significant value (0.001 < 0.005). The results of the hypothesis testing of work discipline and work motivation have been found to have a significant effect on employee performance (F count 142.346 > F table 3.16) and a significant value (0.001 < 0.005).